Separatrix parameters and core performances across the WEST L-mode database. (1st May 2023) - Bourdelle, C.; Morales, J.; Artaud, J.F.; Grover, O.; Radenac, T.; Bucalossi, J.; Camenen, Y.; Ciraolo, G.; Clairet, F.; Dumont, R.; Fedorczak, N.; Gaspar, J.; et al.
Abstract: WEST database analysis shows a correlation of the recycled neutral source around the separatrix with core performances. This observation questions the causality chain between particle source and turbulent transport up to the core in L-mode, high recycling plasmas, an unavoidable phase of all scenarios. The best core performances correlate with the lowest values of the density at the separatrix, n sep, similarly to ASDEX Upgrade (AUG) tokamak and Joint European Torus (JET) tokamak in H-mode (Verdoolaege et al 2021 Nucl. Fusion 61 076006). Reflectometry in the midplane provides n sep, while the temperature at the separatrix, T sep is inferred by the 'two-point model' using Langmuir probe data on divertor targets. Lower separatrix resistivity does not correlate with better core performances, unlike H-mode observations (Eich et al 2020 Nucl. Fusion 60 056016). As expected in the presence of an efficient neutral source due to recycling fluxes, n sep correlates with the D recycled particle flux at the divertor measured by visible spectroscopy. Coherently, at a given controlled central line integrated density n ˉ, lower n sep correlates with a larger density gradient around the separatrix as well as a larger global density peaking, n ˉ / ⟨ n ⟩, measured by interferometry. The latter correlates as well with lower collisionality in the core, similarly to JET and AUG H-modes (Angioni et al 2007 Nucl. Fusion 47 1326). The correlations reported allow phrasing the subsequent causality question: what is the interplay chain between low neutral recycling at the divertor plates, low density at the separatrix, high density peaking at the separatrix, high global density peaking, higher central temperature and better core energy confinement quality? Understanding the causality chain is essential to prepare ITER operation and design DEMO scenarios where the ratio of the divertor leg to the ionization length will be larger and where the pumped flux with respect to the plasma volume will be lower than presently operating tokamaks.